CLASTIC SEDIMENT SOURCE CHARACTERISATION USING DISCRETE AND INCLUDED MAGNETIC PARTICLES - THEIR RELATIONSHIP TO CONVENTIONAL PETROGRAPHIC METHODS IN EARLY PLEISTOCENE FLUVIAL-GLACIAL SEDIMENTS, UPPER DON RIVER BASIN (RUSSIA) - Alekseeva V.A.; Hounslow M.W. (My University, 2004)
Data from mineral magnetics, heavy mineral and quartz grain micromorphology analysis are compared, from early Pleistocene glacial sediments in the River Don palaeo-valley (central part of the Russian Plain). The aim was to evaluate the relative sensitivity of discrete and included magnetic particle populations to depositional processes, sediment provenance and particle size fractionation. Two size fractions from each sample were used for the magnetic measurements, 0.5 1 and 0.25 0.5 mm, on both the original fractions and after acid dissolution to isolate the magnetic inclusions. Quartz micromorphology was assessed on the 0.25 0.5 mm fraction, and is an indicator of the depositional environment and transport process. This shows three morphological groups, whose abundance in each section appears unrelated to their geographic position in the palaeo-valley. The heavy mineral data on the 0.1 0.25 mm fraction, shows a difference in the relative content of sediment derived from a Scandinavian source, mainly reflected in the epidote and amphibole content. The content of Fe-oxides reflects this Scandinavian source by its larger magnetic abundance parameters and lesser haematite content. The discriminating power of magnetic data for separating sediment provenance is not the same across the two studied grain size fractions. The discrete magnetic particles seem to be more powerful in the finer fraction and the included magnetic particles in the coarser fraction. These data show that combined discrete and included mineral magnetic approach offers potentially complementary and powerful means of characterizing glacial sediments for purposes of provenance indication.
Keywords: Sediment provenance; Magnetic inclusions; Environmental magnetism; Quartz micromorphology; Heavy minerals; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен